Definicja piękna w XII wieku a architektoniczna ekspozycja ołtarza w epoce gotyckiej - Mirosław Bogdan (Polonia Sacra)
This article, while taking into account the mystical reality of a relic, defines gothic initiated by the abbot Surger with the construction of the first gothic basilica in Saint-Denis near Paris in the XII century, as a reality required to know the difference between individual invisible beauty and corporeal visible beauty. When the differentiation of these types of beauty shows itself, not only thanks to the unknown in Romanism mystical structure of architecture in a gothic temple, but also through the construction of the gothic altar and hiding it in a choir enclosed by a lectorium in accordance to the zone of aisles, there is a necessity for a scientific definition of beauty connected with the then contemporary stylistic changes.